PEMBENTUKAN KARAKTER DI KALANGAN SISWA MELALUI MATA PEMBELAJARAN PPKn KELAS XI IPS DI SMAS HANG TUAH BELAWAN JL. KAPTEN RADEN SULIAN BELAWAN KECAMATAN MEDAN BELAWAN KOTA MEDAN - Khairun Nisak Sembiring; Syarifah Syarifah (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine character formation through Civics lessons in class XI IPS at SMAS Hang Tuah Belawan. Jl. Captain Raden Sulian Belawan. Medan Belawan District, Medan City. There are two variables in this study, namely the formation of student character (X) and PPKn subjects (Y). In this study, the population was all students of class XI IPS SMAS Hang Tuah Belawan, totaling 262 students. The instrument used in this data collection is a questionnaire about the formation of student character and Civics learning subjects. The data analysis technique used is descriptive quantitative using the product moment correlation coefficient formula to find the relationship between variables (X) and (Y). In this study, it can make a contribution to improving the quality of education which is developed to shape the character of students through PPKn learning subjects.